"A Peculiar People" : Anti-Mormonism and the Making of Religion in Nineteenth-Century America - Fluhman, J. Spencer (Book collections on Project MUSE., 2012)
Though the U.S. Constitution guarantees the free exercise of religion, it does not specify what counts as a religion. From its founding in the 1830s, Mormonism, a homegrown American faith, drew thousands of converts but far more critics. In A Peculiar People, J. Spencer Fluhman offers a comprehensive history of anti-Mormon thought and the associated passionate debates about religious authenticity in nineteenth-century America. He argues that understanding anti-Mormonism provides critical insight into the American psyche because Mormonism became a potent symbol around which ideas about religion.